Pharmaceutical substances : syntheses, patents, and applications of the most relevant AIPs. - Kleemann, Axel (Thieme, 2009)
Pharmaceutical Substances is designed to be a complete reference guide to every pharmaceutical compound of significance. It provides a compendium of some 2,600 active pharmaceutical ingredients (API's) of interest to the chemical and pharmaceutical industries.